Fostering Innovation: Psychological Safety and Gen-Z's Proactive Spirit in Startups - Hendry Hartono; Westin Chandra; Ahmad Syamil; Tri Cahyo Nugroho (Jurnal Penelitian, 2025)
This study investigates the evolving roles of employees in Indonesia's dynamic startup ecosystem, focusing on the proactive behaviors of Gen Z workers as the country approaches its 2030 and 2045 goals. It addresses the problem of how inclusive leadership influences taking-charge behavior among these employees, with psychological safety and workplace thriving as mediators. This research lies in its specific examination of inclusive leadership within Indonesia's startup culture, a topic that has not been adequately explored. The study employs a quantitative approach utilizing SEM-PLS and Warp-PLS software. Data were collected via surveys from 210 Gen Z employees working in Indonesian startups, allowing for a robust analysis of the relationships between inclusive leadership, taking-charge behavior, and the mediating factors. Finding/Results: The findings indicate that inclusive leadership significantly enhances taking-charge behavior, both directly and indirectly through the mediators of psychological safety and workplace thriving. This underscores the importance of fostering an inclusive environment to promote proactive employee behaviors. Enhancing psychological safety and thriving at work can amplify the positive effects of inclusive leadership on employee proactiveness, with recommendations for future research to explore additional mediators and cultural contexts.